The Impact of Sputnik SARS-CoV-2 Vaccines on Antibody Response in the Egyptian Population - Ismail, Ghada; Abdelhamid, Dalia; Mostafa, Marwa Salah; Fahim, Noha Alaa Eldin; Elshafei, Ahmed; Abdelghaffar, Hossam; Naguib, Nashwa; Taher, Omnia; Asker, Menna (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: The coronavirus disease 2019 (COVID-2019) causes the severe contagious acute respiratory syndrome. Therefore, massive vaccination campaign is mandatory to control the spread. Sputnik COVID-19 vaccines induce immunity through different mechanisms involving antibody response that bind to the spike protein to neutralize the viral entry into the cells. AIM: This study aims to compare the titers of specific antibodies in the pre- and post-vaccination sera in the vaccinated Egyptian population to evaluate the efficacy of the sputnik vaccine. METHODS: Samples were collected from 205 adult volunteers receiving the Sputnik vaccine in the Reference Laboratory of Egyptian University Hospitals. Samples were collected before vaccination and within 1, 2, or 3 months after receiving two doses of Sputnik SARS-CoV-2 vaccines from August to October 2021, serum samples collected were tested by quantitative chemiluminescent immunoassay using (Mindray CL-960i chemiluminescence analyzer, India) at the Reference laboratory of Egyptian University Hospitals for neutralizing antibodies, anti-spike antibodies, and total antibody levels before and after vaccination. RESULTS: The results of the 205 paired samples illustrated that there was a statistically significant difference between pre- and post-vaccination antibody levels with a p-value of (< 0.001) indicating that the vaccine produced significantly high levels of antibodies. CONCLUSION: COVID-19 Sputnik vaccines induce immunity through an antibody response that binds to the virus to neutralize its entry into cells. Our study showed a significant increase in the measured post-vaccination levels of the three antibodies among the enrolled volunteers compared to the basal pre-vaccination level and thus sputnik vaccine protects against SARS-CoV-2 infections.